Preoperative malnutrition is associated with increased mortality and adverse outcomes after paediatric cardiac surgery. (19th June 2017) - Ross, Faith; Latham, Gregory; Joffe, Denise; Richards, Michael; Geiduschek, Jeremy; Eisses, Michael; Thompson, Douglas; Radman, Monique
Abstract: Background: Malnutrition is common in children with CHD and is likely to place them at an increased risk for adverse surgical outcomes. We sought to evaluate the impact of preoperative malnutrition on outcomes after paediatric cardiac surgery. Methods: We conducted a retrospective analysis of patients from age 0 to 5 years undergoing cardiac surgery at Seattle Children's Hospital from 2006 to 2015. We used regression modelling to examine the impact of malnutrition on surgical outcomes. Results: We found a non-linear relationship between low height-for-age and weight-for-age z-scores and mortality after surgery. In the range of z-score ⩽−2, each additional unit decrease in height-for-age or weight-for-age z-score was associated with a 2.9 or 2.1% increased risk for mortality, respectively. Each unit decrease in height-for-age z-score was associated with a 1.2% increased risk for cardiac arrest, 1.1% increased risk for infection, and an average of 1.7 additional hours of mechanical ventilation, 6 hours longer ICU stay, and 13 hours longer hospital stay. Each unit decrease in weight-for-age z-score was associated with a 0.7% increased risk for cardiac arrest, 0.8% increased risk for infection, and an average of 1.9 additional hours of mechanical ventilation and 5.3 additional hours of ICU stay. Conclusions: This study is unique in demonstrating a significant association between malnutrition and 30-day mortality and other adverse outcomes after paediatric cardiac surgery in a mixed population of CHD patients. By evaluating nutritional status as a continuous variable, we were able to clearly distinguish the point at which malnutrition begins to affect mortality.